Drepanolejeunea pinnatiloba Schiffn. (Lejeuneaceae): a rare species in Brazil rediscovered after 17 years - Luciana Carvalho dos Reis; Hermeson Cassiano de Oliveira; Kátia Cavalcanti Pôrto (Check List, 2020)
Drepanolejeunea pinnatiloba Schiffn. (Lejeuneaceae) has only been collected once in Brazil, from a single population in the Atlantic Forest in southern Bahia state. Seventeen years later, we report the second record of D. pinnatiloba. This new record is from the Una Biological Reserve, also in southern Bahia. We discuss the geographic distribution and evaluate conservation status of this species for Brazil and the Neotropical region.